Das französische Ancien Régime als Eigentümergesellschaft? - Derouet, Bernard; Fertig, Georg; Guéry, Alain; Kopsidis, Michael (2024)
Bernard Derouet was a highly specialized researcher who regularly published articles about rural French society in Europe's most renowned social and economy history journal, the Annales ESC / Annales HSS. This translation of five selected articles allows German scholars in the fields of social and economic history to continue working directly with intellectual sources from French research.